Community and Controversy: Jews, Anglicans, and Biblical Criticism in Mid-Victorian England - Breuer, Edward (AJS review, 2021)
Mid-nineteenth-century Victorian England was roiled by public controversies regarding the legitimacy of biblical criticism, largely fueled by Anglicans and the Church of England establishment. Jews were well aware of these public controversies and even spoke out in a forthright manner. At this very juncture there was also a rather remarkable Jewish scholar, Marcus Kalisch, who began to advance critical notions in his commentary to the Pentateuch, ultimately coming to conclusions not altogether different from the leading critical scholars in Germany. This article explores the way in which Anglo-Jews first avoided, and then finally confronted, Kalisch's work, and what that said about communal sensitivities and self-consciousness.